Behavioral Prevention of Sexual Transmitted Infections in Female Sexual Workers in Puncak, Bogor - Munaya Fauziah; Nayla Nur Rabbany (International Journal of Healthcare Research, 2018)
Background: Case of HIV/AIDS in the Bogor district each year continues to rise. And one of them caused by free sex. District Cisarua is one of 14 districts highest number of cases of HIV/AIDS.Objective : This study aimed to analyze information about behaviors prevention of Sexually Transmitted Infections (STIs) in Female Sex Workers (FSWs) in Bogor 2016.Methodology: This study which was implemented in July 2016, and used a qualitative approach with key informants is Female Sexual Workers and Security Guards Hotel. Data analysis was done by the content analysis method by transcribing interviews that comes from informants.Result:The results of this research note that informant is Female Sexual Workers due to economic factors. While on Sexually Transmitted Infections prevention behaviors, informants on Sexual Transmitted Infections prevention behaviors by using condoms protective. However, in the perception of the prevention of sexually transmitted infections, the informant use of antibiotics, betel leaves, antiseptic and cleaning themselves after sexual intercourse to maintain health and prevent sexually transmitted infections.Conclusion:In this study of Behavioral Prevention of Sexual Transmitted Infections in Women Sexual Workers by using condoms protective and use of antibiotics, betel leaves, antiseptic and cleaning themselves after sexual intercourse. And suggested to the health department to provide information about Sexually Transmitted Infections more intent, and have a strategy with exciting promotional media which easy to understand by Women Sexual Workers.